Evaluation of medium chain fatty acid (MCFA) supplementation in nursery pig diets - Maurer, Ryan T.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Increased consumer pressure has motivated the pork industry to seek antibiotic alternatives that provide a similar response in growth performance. One possible alternative is medium chain fatty acids (MCFA), but there is limited research evaluating their response. The objective of this study was to compare the effects of MCFA-based products, carbadox, and ZnO on nursery growth performance. A total of 360 nursery pigs (DNA 200×400; initially 5.4 ± 0.07 kg; 21 d if age) were fed one of the following treatments: 1) negative control; 2) 3,000ppm ZnO in Phase 1, 1,500ppm ZnO in Phase 2; 3) 50g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Treatments were fed in two phases (d 0 to 7; d 7 to 19) followed by a common diet (d 20 to 35). A completely randomized design was used with 6 pigs/pen and 10 pens/treatment. Feeders and pigs were weighed weekly to determine ADG, ADFI, and G:F. Data was analyzed using PROC GLMMIX (SAS version 9.4; Cary, NC). Overall (d 0 to 35), pigs fed ZnO and carbadox had greater (P<0.05) ADG and ADFI, than pigs fed FORMI, R2, C6:C8:C10, or the negative control. Pigs fed FORMI and C6:C8:C10 had similar (P<0.05) ADG and ADFI, while R2 had decreased (P<0.05) ADG and ADFI compared to pigs fed the negative control. There was no significance in overall G:F (P=0.32). Due to the variable results of the three MCFA-products used in this experiment, further research is needed to warrant specific MCFA-products as viable substitutions for carbadox or ZnO in nursery pig diets.
Keywords: Spring 2019